O PROCESSO EROSIVO NA BACIA DO ALTO PARAGUAI - Fiori, Alberto Pio; Fiori, Chisato Oka; Disperati, Leonardo; Conceição, Antônio; Kozciak, Simone; Guedes, Jocimar Aparecida; Ciali, Alessandro (Boletim Paranaense de Geociências, 2001)
O Pantanal Matogrossense pode ser subdividido nas províncias fisiográficas de Planaltos, Pantanais e Morrarias, com feições geológicas, geomorfológicas, hidrológicas e pedológicas distintas. Nos Planaltos, grandes extensões de florestas e cerrado sofreram desflorestamento e foram substituídas por atividades agropecuárias, a partir dos anos 70. Como conseqüência, o processo erosivo sofreu uma grande aceleração, levando à perda de grandes porções de terras produtivas e assoreamentos na bacia do Pantanal. O objetivo deste trabalho é avaliar as modificações do uso e ocupação do solo nos últimos trinta anos e suas conseqüências no processo erosivo da região. A análise foi feita em três diferentes momentos: 1966, 1985 e 1996, fazendo-se uso de imagens de satélite TM 5 e de cartas topográficas do IBGE em escala 1: 250.000. Quatro áreas-piloto foram selecionadas para estudos mais detalhados: bacia do rio Taquarizinho, na parte leste da área; região de Pedro Gomes, nas proximidades da divisa dos estados de Mato Grosso e Mato Grosso do Sul; bacias do rios Arica-Açu e Arica-Mirim, na parte norte da bacia e a Chapada do rio Correntes/ Itiquira. Nas três primeiras áreas, foi feito o cálculo de perdas de solos por erosão laminar através do emprego da Equação Universal de Perdas de Solo, em ambiente SIG. Os resultados obtidos colocam em evidência a dinâmica ambiental ocorrida na região, nos últimos trinta anos. THE EROSION PROCESS ON ALTO PARAGUAI WATERSHED Abstract The Pantanal Matogrossense can be subdivided into three physiographic provinces, Planaltos, Pantanais and Morrarias, characterized by peculiar geologic, geomorphologic, hydrologic and pedologic features. On the Planaltos province, large extensions of florestas and cerrados, have been submitted to deforestation and were replaced by farming and cattle raising activities from the 70´s years. In the process of transformation, the deforestation is normally done by burnt or extracted trees with the use of weight agricultural machines. As a consequence of that activity, the erosive process suffered a great acceleration, taking to loss portions of productive lands and flooding of low areas in the Pantanal basin (figure 1). The aim of the present paper is to evaluate the changes on the use and occupation of the soil in the last thirty years and theirs consequences on the erosive process of the region. It has been analyzed in three different moments : 1966, 1985 and 1996 (figures 2 and 5). Statistical analysis of multitemporal data base were carried out to compare the land cover changes in these provinces. The 66´s data was available from the DSG/IBGE (Geographic Division of Brazilian Army and Brazilian Institute for Geography and Statistics); the 1985 and 1996 data have been obtained from Landsat TM images interpretation. Four pilot areas were chosen for detailed study: the Taquarizinho basin, located southern from Coxim (figure 6 and tables 1, 2 and 3), the Arica-Açu and Arica-Mirim basins (figures 7 and 8), on the northern part of Alto Paraguai Basin, the Pedro Gomes region (figures 9 and 10 and table 4) and the rio Correntes / Itiquira Chapada (figures 11, 12 and 13). The laminar erosion on the first three areas was calculated with the application of the Universal Soil Loss Equation, aided by Geographic Information System and Remote Sensing techniques. The results obtained put in evidence the environmental dynamic occurred on the Pantanal region in the last thirty years.